ANALISIS PERUBAHAN HUTAN MANGROVE MENGGUNAKAN DATA PENGINDERAAN JAUH DI PANTAI BAHAGIA, MUARA GEMBONG, BEKASI - Nana Suwargana (Indonesian National Institute of Aeronautics and Space (LAPAN), 2008)
TMangrove forests grow near the big river estuary where the river delta gives a lot of sediment (sand and mud). Mangrove roots collect sediments and slow the water flow to protect the coastline and prevent the erosion. Along the time, the roots can collect mud to extend the edge of the coastline. The purpose of this study was to analyze the changes of mangrove forests, coastline, and its effect on the income of fishermen on the Bahagia coast, Muara Gembong, Bekasi, West Java Province during 17 years between 1990 and 2007. Observations were made by using two series of multitemporal (Landsat- TM 1990 and SPOT-4 2007) data. Information about the distribution, extent and land cover changes to analyze the value was obtained by the spectral based (RGB 453 Landsat-TM and RGB 143 SPOT-4) color composite image, image classification, and field data. While information on the coastline change based on the 2007 classified images was overlayed with the classified images in 1990. Multitemporal data analysis results show that: 1). mangrove forest changes during the 17 years (1990-2007) has decreased from 34.89 hectares to 33.23 hectares and the results of overlaying the image of the coastline of classification image in 2007 with the coastline of classification image in 1990 found that there coastline abrasion occurs and accretion; 2). conditions of the existence of mangrove forests in coast Bahagia with a dwindling population have affected the income of fishermen nearby. Keywords:Multitemporal, Color composite, Image classification, Mangroves, Coastline, Abrasion, and accretion